Conceptual feasibility studies for cost-efficient and bi-functional methylcyclohexane dehydrogenation in a membrane reactor for H2 storage and production. (1st January 2021) - Byun, Manhee; Kim, Heehyang; Choe, Changgwon; Lim, Hankwon
Highlights: Techno-econoic and carbon footprint analysis for methylcyclohexane dehydrogenation in a membrane reactor (MR). Levelized costs of H2 (LCOHs) for various H2 capacities obtained. Effects of each techno-economic parameter on LCOH confirmed. CO2 emissions from both a packed-bed reactor and an MR compared. Abstract: As the global trend towards transition to a "hydrogen society" continues to gain momentum, a lot of studies on alternative hydrogen (H2 ) production methods are on the rise. Among them, methylcyclohexane (MCH) dehydrogenation in a membrane reactor (MR) is reported here as one possible candidate, affording its enhanced H2 yield and a compact design. In this study, techno-economic analysis and carbon footprint analysis (CFA) of MCH dehydrogenation in an MR are carried out to investigate economic and environmental feasibility providing techno-economic and environmental guidelines for realizing it as mature technology. The economic parameters are determined through process simulation using Aspen Plus®, and the unit H2 production costs are obtained for a packed-bed reactor (PBR) and an MR in H2 production capacities of 30, 100, 300, and 700 m 3 h −1 . The effects of each economic parameter on the unit H2 production cost are identified through sensitivity analysis (SA) and scenario analysis is performed under various conditions to investigate the effects of technical parameters of the membrane, such as the H2 production capacity, temperature, and H2 permeance on the unit H2 production costs. CFA is also performed to investigate the environmental feasibility of MCH dehydrogenation in an MR by considering CO2 emissions at each part.